(untitled) - Altucher, James (Hoboken, N.J., 2005)
Trade Like Warren Buffett challenges the current coverage of this great investor by including details of all of Buffett's investing and trading methods, including mean reversion, commodities, bonds, arbitrage, market timing, funds, as well as Graham-Dodd. In addition to the value investing approach, this book discusses other, lesser-known trading strategies and techniques that have helped to make Buffett the greatest investor in history. To augment the discussion of each strategy, Trade Like Warren Buffett also includes interviews with leading financial professionals, who reveal in detail how they've successfully used the same techniques
Keywords: Investments,Đầu tư,Buffett, Warren